Sustainable growth as a result of implementing the concept of sustainable development of Chinese companies - A. O. Volodina; M. B. Trachenko (Вестник университета, 2024)
The article discusses two currently relevant concepts such as sustainable development and sustainable growth. By analyzing the sustainable growth factors of 48 ESG-oriented listed Chinese companies for the period 2020–2022, the authors have proved that following the sustainable development concept can ensure the sustainable growth of companies’ performance. ESG- oriented companies show an increase in the level of generated profits and profitability, as well as a decrease in the debt-equity ratio, which positively characterizes their performance. Excess of actual growth of such companies over sustainable growth has been revealed, which does not lead to negative consequences of the activity for the analyzed period, and also does not increase the risks associated with the need to increase debt capital to ensure the identified growth. The study concludes that it is necessary to develop a new toolkit or integrate the two concepts considered to ensure the ability of companies to achieve their sustainability goals without compromising fundamental financial performance. The study results can be used by companies that are already following the sustainable development concept, as well as by those ones that are only at the initial stage of developing and implementing ESG indicators in their operations, by investors when selecting an investment target and by academics in the course of research devoted to the topic of sustainable development and sustainable growth.